FINANCIAL PLANNING ANALYSIS IN MAINTAINING MSME BUSINESS CONTINUITY - wiwik wahyuningsih (Al-Qalam Institute, Probolinggo, East Java, Indonesia, 2024)
When running a business, financial management is important for all MSME actors to implement. Finance is an important point in maintaining the viability of a business. The purpose of this study is to analyze financial management practices by SMEs. During a pandemic, management is an important matter for business actors to pay attention to. This type of research is descriptive qualitative. The data source obtained is obtained from the results of interviews and observations. The interviewees were selected using the snowball sampling technique taken from several SMEs. The analysis tool is thematic analysis. With indicators of financial planning, implementation and financial reporting, and financial control. The results of the study show that MSME actors have implemented financial planning, but implementation and control have not been implemented properly. This is due to the lack of human resource capabilities, time constraints and low level of awareness of the importance of business financial management.